De siderúrgica a turística : Breve historia ocupacional de la ciudad de Palpalá (Jujuy-Argentina) - Bergesio, Liliana (Revista de estudios regionales y mercado de trabajo.)
The growth of Palpalá City (Province of Jujuy, argentina) since the 1940s, is linked to altos Hornos Zapla (ahz) the state-owned steel and iron company whose privatization in the early 1990s as part of the external three-sided opening, privatizations and deregulation which characterized convertibility, meant large changes in the local economic structure. In the 1950s, this city was identified by the town hall as 'mother of Industries' ('madre de Industrias'), whereas today, the municipal slogan is 'City of Tourism' ('Ciudad Turística'). Recovering the recent occupational history of this city meets the need to know the labor and socioeconomic reality of this urban area in the Province of Jujuy, about which information is rare. Although it is included in the Home Survey?s sample, it is shown in blocks, making the information very limited. It is paradigmaticin this city to study the means chosen to try to overcome the traumatic shock that ahz's privatization meant, to analyze the policies developed and evaluate their results, some years after their application. In Palpalá, a local development strategy was applied, with a strong impulse to micro-businesses, following, somehow, the model postulated at national level, what will allow us to know the local reality better, as well as the regional and national realities for its characteristics. The methodology used in this work ('From iron and steel industry to tourist city. Brief occupational history of Palpala city) was the bibliographic research of the rare existing studies, interviews to qualified informers as well as the use of secondary data sources, such as data from different national Censuses. To conclude, it can be said that due to the crisis of the 1990s and its state reducing plan, those who suffered its consequences less are, paradoxically, those who are still related to state jobs. In Palpalá, when ahz was privatized and the buyer company failed to fulfill its contract duly, leaving a great number of the local people unemployed, it was the municipal government who had to assume the responsibility of an answer ( in this case, through training, credit and/or counseling to micro-businessmen) In the last years, however, the possibility to work in informal activities has become important in Palpalá, with a high percentage of people working in city fairs selling different kinds of goods. although the change in the model in the recent years has allowed the reactivation in different areas, a preliminary evaluation is that the improvement does not seem to have reached the core of excluded and marginalized of the previous decade